Cosmetic composition comprising natural polymer - JUNG SEO-HEE; SHIN HYEOK-JUN; KIM MOON-JU (2022)
A cosmetic composition comprising a natural polymer. The oil-in-water cosmetic composition according to the present invention uses a natural polymer instead of a synthetic polymer comprising a polyethylene glycol-based surfactant, while containing a fatty alcohol, a lecithin-based surfactant, and an anionic surfactant in the composition together, as a result, it is possible to provide a cosmetic composition which has little change in viscosity and particle size over time, does not precipitate at high and low temperatures, and has excellent emulsion stability. 包含天然聚合物的化妆料组合物。根据本发明的水包油型化妆料组合物使用天然聚合物来代替包含聚乙二醇类表面活性剂的合成聚合物，同时在组合物中一起包含脂肪醇、卵磷脂类表面活性剂以及阴离子类表面活性剂，从而可以提供随时间流逝的粘度变化和颗粒大小变化较小，同时在高温及低温下组合物不会析出，并且乳化稳定性优异的化妆料组合物。